The Relationship Of Program Implementation With Students’ Interest in Participating Judo Extracurricularies At Genus Bukittinggi Vocational School - Haryasa, Najeli Engla; Natsir, MHD (Universitas Negeri Padang, 2023)
The aim of this research is to determine the relationship between program implementation and students' interest in participating in judo extracurriculars at Genus Vocational High Scholl Bukittinggi. This research uses a correlational quantitative approach. The population of this study was the elevent and twelve class of Genus Bukittinggi Vocational School students, namely 35 students. The sampling technique in this research was carried out using a probability sampling technique, so the number of samples for this research was 30 Genus Bukittinggi Vocational School students. Data collection techniques through distribution of questionnaires to research respondents, data analysis techniques using percentages to find correlations using the product moment formula. The results of this research are: 1.) The implementation of the judo extracurricular program at GENUS Vocational School, Bukittinggi City is low, 2.) Student interest in participating in judo extracurriculars at GENUS Vocational School, Bukittinggi City is low and 3.) There is a significant relationship between the implementation of extracurricular programs and student interest. Participated in extracurricular judo at Gema Nusantara Vocational School, Bukittinggi.